Power Coordinated Control and Parameter Analysis for Spiral Spring Energy Storage Systems Based on Backstepping Control Under Current Vector Orientation - Yu, Yang; Wang, Mengyun; Zhang, Ruifeng; Mi, Zengqiang; Zheng, Xiaoming (Frontiers in Energy Research, 2022)
As a new and great source of potential energy storage technology, the spiral spring energy storage (SSES) technology uses a permanent magnet synchronous machine (PMSM) to tighten or release the spiral spring for energy conversion. In allusion to the feature of simultaneous variations in torque and inertia for spiral springs in operation, it is difficult for the SSES system to show good control performance in regulating the power from/to the grid under a conventional vector control method. A power coordinated control scheme of the SSES system with the grid is proposed to integrate the grid-side converter (GSC) with the machine-side converter (MSC) based on backstepping control under the current vector orientation. First, the mathematical models of GSC and PMSM under the current vector orientation coordinate frame are established. Second, the coordinated control scheme is designed by the backstepping control principle, and its stability is proved in theory. Then, the optimal control parameters in the control scheme are determined by investigating the desired control performance. Ultimately, the simulation and experimental results show that the proposed control scheme with the chosen control parameters coordinates the GSC and the MSC well. The power signal is tracked accurately and rapidly, and the operation performance of the SSES system and its energy exchange with the grid are both improved effectively.